2015
DOI: 10.1088/0022-3727/48/46/465306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Xe ion (167 MeV) irradiation on polycrystalline SiC implanted with Kr and Xe at room temperature

Abstract: The effect of swift heavy ion (Xe 167 MeV) irradiation on polycrystalline SiC individually implanted with 360 keV Kr and Xe ions at room temperature to fluences of 2×10 16 cm -2 and 1×10 16 cm -2 respectively, was investigated using transmission electron microscopy (TEM), Raman spectroscopy and Rutherford backscattering spectrometry (RBS). Implanted specimens were each irradiated with 167 MeV Xe +26 ions to a fluence of 8.3×10 14 cm -2 at room temperature. It was observed that implantation of 360 keV Kr and Xe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
(40 reference statements)
3
6
0
Order By: Relevance
“…Irradiation of the implanted SiC with Xe (167 MeV) ions at room temperature to fluences of 3.4 × 10 14 and 8.4 × 10 14 cm −2 caused the partial reappearance of the broad Si-C characteristic Raman peaks at around 775 and 900 cm −1 with the C-C (around 1,425 cm −1 ) and Si-Si (around 525 cm −1 ) peaks still present (see Figure 3). The appearance of the SiC characteristic peaks albeit broad indicates some limited recrystallization of the initially amorphous SiClayer.Similar recrystallization of SiC predamaged by different implanted ions after SHIs irradiation has been reported previously (Debelle et al, 2012;Hlatshwayo et al, 2015;Hlatshwayo et al, 2016;Abdelbagi et al, 2019b;Abdelbagi et al, 2022). In our previous studies, transmission electron microscopy (TEM) and Raman spectroscopy were used to study the structural changes of the as-implanted SiC after SHIs irradiation (Hlatshwayo et al, 2015;Hlatshwayo et al, 2016;Abdelbagi et al, 2019b;Abdelbagi et al, 2022).…”
Section: Figuresupporting
confidence: 81%
See 2 more Smart Citations
“…Irradiation of the implanted SiC with Xe (167 MeV) ions at room temperature to fluences of 3.4 × 10 14 and 8.4 × 10 14 cm −2 caused the partial reappearance of the broad Si-C characteristic Raman peaks at around 775 and 900 cm −1 with the C-C (around 1,425 cm −1 ) and Si-Si (around 525 cm −1 ) peaks still present (see Figure 3). The appearance of the SiC characteristic peaks albeit broad indicates some limited recrystallization of the initially amorphous SiClayer.Similar recrystallization of SiC predamaged by different implanted ions after SHIs irradiation has been reported previously (Debelle et al, 2012;Hlatshwayo et al, 2015;Hlatshwayo et al, 2016;Abdelbagi et al, 2019b;Abdelbagi et al, 2022). In our previous studies, transmission electron microscopy (TEM) and Raman spectroscopy were used to study the structural changes of the as-implanted SiC after SHIs irradiation (Hlatshwayo et al, 2015;Hlatshwayo et al, 2016;Abdelbagi et al, 2019b;Abdelbagi et al, 2022).…”
Section: Figuresupporting
confidence: 81%
“…It has been reported in the previous studies that the irradiation of SiC with ions of energies E< 0.5 MeV amorphized SiC depending on the irradiation fluence, temperature and ion mass (Wendler et al, 1998;Weber et al, 2001;Debelle et al, 2010;Abdelbagi et al, 2019a;Abdelbagi et al, 2019b). However, the recrystallization of an initially damaged/amorphous layer of polycrystalline SiC was observed after irradiation by SHIs at room temperature and 500 °C (Hlatshwayo et al, 2015;Hlatshwayo et al, 2016;Abdelbagi et al, 2019a;Abdelbagi et al, 2019b). This was due to the SHIs(with energy >5 MeV) transferring their energy into the target electrons in the bombardment process which cause thermal spikes depending on the energy transferred, i.e., electronic stopping power (Debelle et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A crucial approach for designing radiation resistant materials is to promote an efficient recovery of irradiation-induced defects as soon as they form [19], [20]. Recent studies have shown that tailoring the grain size of SiC by making it nanocrystalline (grain sizes <100 nm) introduces a high number of defect sinks [21], [22] greatly improving its radiation tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus essential to study SiC behavior under irradiation of such heavy element especially in terms of Xe retention, amorphization and material swelling. Few studies have examined the behavior of Xe in SiC [6][7][8][9][10] but the effect of SiC crystalline microstructure on such irradiation behavior is not completely understood, especially at high fluence. This is the main target of the present work.…”
Section: Introductionmentioning
confidence: 99%